Environment and the formation of galaxies: 30 years later proceedings of Symposium 2 of JENAM 2010 - Ferreras, Ignacio; Pasquali, Anna (Heidelberg, Germany Springer Berlin, 2011)
The publication of the morphology - density relation by Alan Dressler in 1980 brought into the limelight the role played by environment in the formation and evolution of galaxies. The symposium Environment and the Formation of Galaxies: 30 years later, was organised with the purpose of establishing the environmental impact on the evolution of galaxies and its dependence on look-back time. Special emphasis was placed on the physical mechanisms that are responsible for transforming galaxies once they are accreted by a group or a cluster, including the observable imprint left in the galaxy HI distribution. Other major topics of the symposium were the environmental dependence of galaxy properties at z 1 and the implementation of environmental effects in cosmological models of galaxy formation and evolution. This book presents the edited proceedings of this stimulating meeting
The Morphology-Density Relationship Looking Back, Thinking Back -- The Cosmic Mass Density Field Reconstruction from the SDSS Group Catalog -- The Void Galaxy Survey -- Metallicities of galaxies in the Lynx-Cancer void -- The dependence of low redshift galaxy properties on environment -- The VIMOS VLT Deep Survey: a homogeneous galaxy group catalogue up to z ~ 1 -- The fossil candidate RX J1548.9+0851 -- Measuring the halo mass function in loose groups -- The environments of Luminous Infrared Galaxies -- UV-IR luminosity functions and stellar mass functions of galaxies in the Shapley supercluster core -- Component Luminosity Functions of Galaxy Pairs in the MGC -- The Hercules cluster environment impact on the chemical history of star-forming galaxies -- The Symbiotic Relationship Between the Evolution of Galaxy Groups and their Resident Galaxies -- Lopsidedness in WHISP galaxies -- The Fundamental Plane of early-type galaxies: environmental dependence from g through K -- On galaxy mass-radius relationship -- And the winner is: galaxy mass -- Ages of globular cluster systems and the relation to galaxy morphology -- AGN feedback and quenching of star formation: a multiwavelength approach with the EURO-VO -- Does environment affect the star formation histories of early-type galaxies? -- Revealing the origins of S0 galaxies using maximum likelihood analysis of PNe 2D kinematics: the role of environment -- Stellar populations in the outskirts of M33 -- Are boxy/disky Ellipticals dependent on Environment? -- An environmental Butcher-Oemler effect in intermediate redshift X-ray clusters -- Testing the Hierarchical Scenario with Field Disk Galaxy Evolution -- The effect of the environment on the gas kinematics and morphologies of distant galaxies -- Deprojecting the quenching of star formation in and near clusters -- Simulations of star counts and galaxies towards Vista Variables In The Via L´actea survey region -- Nature and nurture of early-type dwarf galaxies in low density environments -- Galaxy evolution in clusters since z ~ 1 -- The HAWK-I cluster survey -- 3D spectroscopy unveils massive galaxy formation modes at high-z -- Detailed stellar population analysis of galaxy clusters at increasing redshift: a constrain for their evolution -- The role of galaxy stellar mass in the colour-density relation up to z ~ 1 -- Selection of Luminous Galaxies at the Edge of the Universe -- From fields to a super-cluster: the role of the environment at z=0.84 with HiZELS -- Witnessing a link between starburst and AGN activities at 2 < z < 4? -- Galaxy properties in different environments at z > 1.5 in the GOODS-NICMOS Survey -- Simulations of shell galaxies with GADGET-2: Multi-generation shell systems -- Comparing Various Approaches to Simulating the Formation of Shell Galaxies -- Modelling the evolution of galaxies as a function of environment -- Reconciling a significant hierarchical assembly of massive early-type galaxies at z 1 with mass downsizing -- The Origin of the Morphology-Density Relation -- Towards Understanding Simulations of Galaxy Formation -- Quadruple-peaked Line-of-sight Velocity Distributions in Shell Galaxies -- Tidal Stirring of Milky Way Satellites: A Simple Picture with the Integrated Tidal Force -- Ram pressure stripping of hot galactic halos in galaxy clusters -- The transformation of Virgo galaxies under the influence of ram pressure -- Gravity at Work: How the Build-Up of Environments Shape Galaxy Properties.
Electronic reproduction.
Keywords: Galaxies; Astronomy